PERILAKU MENYIKAT GIGI PADA ANAK DI SD 3 KOROLOLAKI KECAMATAN PETASIA KABUPATEN MOROWALI UTARA - Talindong, Agustinus; Jumain; Lapato, Sepriyanti; Wahyu (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2022)
Optimal body health is one of which is influenced by supporting factors, namely dental and oral health. Based on the results of interviews, several children explained that they were still not regular in brushing their teeth so that children's teeth had cavities because children were lazy to brush their teeth when going to bed because they were not used to brushing their teeth at night, based on observations of the condition of children's teeth that were not intact or had cavities. The purpose of this study was to determine tooth brushing behavior in children aged 3 Korololaki Elementary School, Petasia District, North Morowali Regency. This type of research is quantitative with a descriptive approach. Tooth brushing behavior variable. Collection using an observation sheet with 20 items for assessment of tooth brushing behavior. Data analysis using univariate analysis. The population in this study were 46 students who attended SD 3 Korololaki in 2022. The sample in this study was 43 respondents. The results showed that the behavior of respondents in the category of needing guidance was 22 respondents (51.2%), the sufficient category was 14 respondents (32.6%), the good category was 4 respondents (9.3%), the very good category was 3 respondents (7.0%). Conclusion The majority of students at SDN 3 Koro-lolaki, Petasia District, North Morowali Regency have behaviors that need guidance in brushing their teeth. Suggestions are that the school is expected to cooperate with the health office in an effort to improve the status of a clean and healthy lifestyle, it is also hoped that this can be used as a reference for adding nursing knowledge, then it is hoped that other researchers can carry out further research on tooth brushing behavior in children which is more than research which have existed